Is diagnostic accuracy of Alvarado scoring feasible in acute surgery for management of acute appendicitis? (Bangladesh Journal of Medical Science, 2016)
Aim: To evaluate the usefulness and feasibility of the Alvarado scoring system in acute surgery in reducing the percentage of negative appendicectomy in our institute.Materials and Methods: A prospective study was conducted, comprising 100 patients, admitted to department of Surgery in Maharishi Markendeshwar Institute of Medical sciences & Research (M.M.I.M.S.R), Mullana, Ambala, India during the period October 2012 to July 2014 with a preliminary diagnosis of acute appendicitis. Patients of both sexes and all age groups were included in the study and their Alvarado scores calculated, on the basis of which patients were divided into three groups: group1 (alv. Score >7) , group 2 (alv. score 5-6), group 3 (alv. Score 7, 8 were having score 5-6 and 1 had score 7, 4 were having score 5-6, and 2 females had scoring